Alcohol use among people living with HIV/AIDS (PLWHA) on Highly Active Antiretroviral Therapy (HAART) at Otjiwarongo ART Clinic and its effects on their adherence to HAART - Chikwati, Enerst Mukono (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.